Prevalence and experiences of intimate partner violence against women with disabilities in Bangladesh: results of an explanatory sequential mixed-method study - Hasan, Tanvir; Muhaddes, Tisa; Camellia, Suborna; Selim, Nasima; Rashid, Sabina (© 2014 SAGE Publications Inc., 2017)
This article was published in the Journal of Interpersonal Violence [© 2014 SAGE Publications Inc.] and The Journal's website is at: http://journals.sagepub.com/doi/abs/10.1177/0886260514534525